Pengalaman Komunikasi Lintas Budaya dalam Membangun Toleransi antara Komunitas Hindu dan Muslim di Desa Sekelor Sidoarjo - Ramzy Ramadhan; Nikmah Suryandari (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2025)
This study aims to describe and analyze the intercultural communication experiences between Hindu and Muslim communities in fostering tolerance in Sekelor Village, Sidoarjo Regency. This village is notable as a minority Hindu community lives harmoniously with the Muslim majority. A descriptive qualitative approach was employed, using interviews, observations, and documentation for data collection. The findings show that communication between the two communities occurs intensively through daily social interactions, cooperation in religious and social activities, and mutual respect for differences. Forms of communication include verbal and non-verbal exchanges practiced within the context of local culture and communal values. Tolerance is reflected not only in accepting differences but also in active participation in each other’s religious events. Supporting factors for this tolerance include a strong awareness of peaceful coexistence, local cultural values, the role of community leaders, and openness to diversity. The study affirms that intercultural communication can serve as a vital bridge in strengthening a pluralistic and harmonious society.